A experi??ncia de mediadores escolares nas situa????es de bullying na rela????o entre professor(a) e aluno(a) - Fidalgo, Adriano Augusto (2019)
Bullying is a relatively recent term that has gained strength primarily in the educational setting to call situations involving depreciation practices of the human person, whether by physical characteristics, gender, race, social status, belief or any other kind of derogatory characterization. In remote times the motives that generated the so-called "mockery" or "joking" among children were commonplace and few people talked about it. Nowadays, with the advancement of society and especially of the Legislation aimed at the protection of the Child and Adolescent, systematic intimidation is not only punishable but also represents the very end in itself of a lack of respect for the similar. When thinking about Bullying through an "action ecology", the present work aims to give a view to the subject from its material condition: the way it occurs in School Institutions. In order to fulfill this objective, the collection of testimonies, the bibliographic review and the legislation pertinent to systematic intimidation were carried out. Through interviews with school mediators, this research aimed to observe how situations of repeated violence occur in the school environment, in the relationship between teachers and students and, in relation to the school mediator, how he positions himself in front of the delicate question. The schools chosen for this research are located in the Board of Education North 02, where all the reports were duly authorized by the interviewees. The results were very useful, because the statements presented by the mediators gave the contours of these eventual conflicts in the coexistence between teachers and students, so that, sometimes, the observed attitudes end up culminating in Bullying situations. It concludes that the repeated intimidation practiced by teachers is common, but must be seen under the light of all the complexity that surrounds the school environment, its power structure, the symbolic power established and the very aggressions suffered by the subjects of the action. In this conflictive environment, mediators play a key role in resolving incidents, mediation of conflicts and among all those involved in the educational process: school, students and community. Intervention at the beginning of conflicts helps to ensure that disagreements do not grow, where investment in prevention, in order to prevent such occurrences from taking on greater proportions, contributes to the improvement of the school microsystem and encourages a more humane and fuller education.